EFFECTIVENESS OF PBL-BASED MOBILE LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Irawati, Irawati; Huda, Nizlel; Adji, Sandra Sukmaning (Jurnal Pendidikan Matematika (JUPITEK), 2022)
The purpose of this research is to evaluate whether or not students in the eighth grade at SMP Negeri 2 Betara in the Tanjung Jabung Barat Regency can improve their mathematical critical thinking skills by using mobile learning that is based on problem-based learning (PBL). The participants in this research were all eighth-graders from one junior high school in the Tanjung Jabung Barat Regency. There were a total of 128 students included in this study, and they were distributed across four classes. The sample was selected from as many as two classes, specifically VIIIA with a total of 28 students serving as the experimental group and VIIIB with a total of 28 students serving as the control group. The analysis of the data reveals that the Zcount value is 10,099, and the significance value is 0.000< 0.005; these values were determined to be significant. Therefore, the working hypothesis or alternative hypothesis that was proposed in this study is accepted. It states that there is a difference in the average critical thinking of students who use PBL-based mobile learning compared to students who use standard teaching materials. While the null or nil hypothesis, which states that "there is no difference in the average critical thinking of students who use PBL-based mobile learning and students who use conventional teaching materials," is rejected.